2006
DOI: 10.1080/07474930500545439
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Power of Bootstrap and Bartlett-Corrected Tests of Hypotheses on the Cointegrating Vectors

Abstract: In this paper we compare Bartlett-corrected, bootstrap, and fast double bootstrap tests on maximum likelihood estimates of cointegration parameters. The key result is that both the bootstrap and the Bartlett-corrected tests must be based on the unrestricted estimates of the cointegrating vectors: procedures based on the restricted estimates have almost no power. The small sample size bias of the asymptotic test appears so severe as to advise strongly against its use with the sample sizes commonly available; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Previous simulation studies of bootstrap tests on co-integrating relations in VAR models include Fachin (2000), Gredenhoff and Jacobson (2001), and Omtzigt and Fachin (2006). Compared to these, the Monte Carlo simulation study reported here differs substantially.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 41%
See 2 more Smart Citations
“…Previous simulation studies of bootstrap tests on co-integrating relations in VAR models include Fachin (2000), Gredenhoff and Jacobson (2001), and Omtzigt and Fachin (2006). Compared to these, the Monte Carlo simulation study reported here differs substantially.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 41%
“…resampling, but instead drawn from a Gaussian distribution with covariance matrixΩ. Finally, Omtzigt and Fachin (2006) compare the aforementioned tests with focus on the unrestricted bootstrap.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They prove bootstrap consistency not only for the OLS estimator and corresponding test statistics, but also for the case of asymptotically efficient estimation and hypothesis testing. Size and power properties of bootstrap hypotheses tests on cointegrating vectors have been compared with Bartlett‐corrected tests in Omtzigt and Fachin () where it is pointed out that both types of tests must be based on the unrestricted estimates of the cointegrating vectors not to lose power. In a reduced rank VAR model, Swensen () applied a residual‐based bootstrap procedure for testing and determining the cointegration rank.…”
Section: Introductionmentioning
confidence: 99%
“…They prove bootstrap consistency not only for the OLS estimator and corresponding test statistics, but also for the case of asymptotically efficient estimation and hypothesis testing. Size and power properties of bootstrap hypotheses tests on cointegrating vectors have been compared with Bartlett-corrected tests in Omtzigt and Fachin (2006) where it is pointed out that both types of tests must be based on the unrestricted estimates of the cointegrating vectors not to lose power. In a reduced the m 2 -dimensional vector that contains the last m 2 D m m 1 coordinates of X t for some 0 Ä m 1 Ä m. In this section, we assume that ¹X t ; t 2 N 0 º is a so-called m-dimensional, full-rank random walk, that is, X t follows the model X t D X t 1 C U t ; t 2 N;…”
Section: Introductionmentioning
confidence: 99%